IMPLEMENTASI MODEL CONTEXTUAL TEACHING AND LEARNING BERBASIS GLOBAL CITIZENSHIP UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KETERAMPILAN BERFIKIR KRITIS SISWA SD - Mulyani, Hastri; Hermita, Neni; Erlisnawati, Erlisnawati (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2024)
This study aims to evaluate the effectiveness of the implementation of the Contextual Teaching and Learning (CTL) Model based on Global Citizenship in improving the conceptual understanding and critical thinking skills of fifth-grade elementary school students. This study uses a Pretest-Posttest Control Group experimental design, where the experimental class is taught using the CTL model based on Global Citizenship, while the control class uses a conventional learning model. The research sample consisted of 86 fifth-grade students at SDN 181 Pekanbaru City, who were randomly divided into two groups. The results showed that the experimental class experienced a significant increase in conceptual understanding and critical thinking skills compared to the control class. This is evidenced by the higher average posttest score in the experimental class compared to the control class. The N-Gain analysis also shows that the CTL Model based on Global Citizenship is included in the effective category for improving students' conceptual understanding and critical thinking skills. The CTL approach, which emphasizes the relevance of subject matter to real-life contexts and global issues, allows students to be more critical in analyzing and applying the knowledge they have learned. This study makes an important contribution to the field of education, especially in efforts to improve the quality of learning to be more relevant and contextual.